Analysis of the Effects of Socioeconomic Determinants on Income Inequality in Regencies and Cities in Java in the 2017-2024 Period - Kamila, Adelia Cahya; Suman, Agus (Journal of Development Economic and Social Studies, 2026)
Java Island contributes the largest share to Indonesia’s Gross Regional Domestic Product (GRDP); however, it continues to experience relatively high income inequality. This study aims to examine the socio-economic determinants of income inequality across regencies and cities on Java Island over the period 2017–2024. The analysis employs panel data regression using the Fixed Effects Model, covering 113 regencies and cities. Income inequality is measured using the Gini ratio, while the explanatory variables include sectoral GRDP (primary, secondary, and tertiary sectors), minimum wage, population size, and the Human Development Index (HDI). The empirical results indicate that GRDP in the primary sector and the minimum wage have a positive and statistically significant effect on income inequality. In contrast, GRDP in the secondary sector significantly reduces income inequality. Meanwhile, GRDP in the tertiary sector, population size, and HDI do not exhibit statistically significant effects on income inequality. These findings suggest that income inequality on Java Island is largely influenced by structural economic transformation. Therefore, policy efforts should focus on strengthening labor-intensive industries, modernizing the primary sector, and designing more inclusive minimum wage policies to mitigate income disparities.